Hubungan antara Higiene Sanitasi Pedagang dengan Keberadaan Bakteri Escherichia Coli pada Milkshake - Sandika, Yogi; Mulasari, Surahma Asti (Universitas Ahmad Dahlan, 2019)
Background: Food including beverages is one of the basic human needs. The high level of human need for water as a beverage makes the producers compete to create innovative products of quality to meet those needs. One of the beverage products is Milkshake. Milkshake is a type of drink that is in great demand with the main ingredients of milk with various flavors and. Because serving milkshakes in cold if unsuitable sanitary hygiene treatment will allow contamination by bacteria especially Escherichia coli (E.coli). Purpose of this research was to know hygiene sanitation relationship of merchant with existence of E.coli in milkshake. Method: Research with observational analytic with cross sectional design. The sampling technique used total sampling with 34 respondents. The research instrument was cheklist to beverage handlers (respondens) sanitation and milkshake. Processing techniques and data analysis with chi square statistical test. Results: Fom the 34 samples taken, 94.1% of the samples are positively containing E.coli. The result of chi-square test with an alpha 0f 5% indicates that the behavior of beverage handlers with the presence of E.coli that are p value 0.037 (Ho is rejected), p value of water sanitary condition: 0.027 (Ho is rejected), p value of tools sanitary conditions: 0.037 (Ho is rejected) and p value for place sanitary condition: 1.000 (Ho received). Conclusion: There was a relationship between the behavior or beverage handlers, the sanitary conditions of water an equipment with the precence of E.coli because p<α=0.05. There was not relationship between the sanitation conditions of place with the presence of intestinal E.coli because of p>α=0.05.